A Note on Blanchard and Kiyotaki (1987). - Claus Thustrup Hansen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1998)
This note reconsiders the private losses and welfare effects of a monetary expansion obtained in the seminal Blanchard & Kiyotaki (1987) article. In the original article it is argued that the welfare ''dependence is a complex one''. Therefore, the authors only present some numerical examples. On the contrary, this note argues that the dependence is relatively simple. It is even possible to derive unambiguous comparative static results. Furthermore, it is shown that figures on both private losses and welfare effects reported in Table 1 and 2 of the article are wrong and new figures are reported.
Keywords: 330